Problems of budget control in public finance management - ShevchukV. О.; Bondaruk, T. H.; Melnychuk, N Yu. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
Budget control is an important constituent in the formation and use of financial resources at all the levels of economic management. Budget control in the public sector is structured in a way enabling the controlled objects and controlling bodies to operate as an integrated management system. Various types of budget control are responsible for effective performance of the public control system. Their use for supervisory purposes enables to create theoretical background for developing new approaches to budget control improvement; it allows to consider the problems caused by ineffective formation and use of financial resources and avoid inaccuracies in preparation, approval, organization and execution of the budget process, to facilitate implementation of realistic assessment of budget programs and enhance the effectiveness of use of the financial resources. It allows for decision making regarding the use of financial resources at various levels to select desired futures scenarios of their development with due consideration to the strategic planning priorities. The article gives a profound rationale of the necessity and importance of budgetary control in public finances system. The authors ’ approach to interpretation of budgetary control as management subsystem, built by the national government, used by the local government to determine the legality of the budget process participants in the preparation, review, approval and implementation of budgets to ensure the effective formation, targeted and appropriate use of financial resources, is given. The authors ’ approach to implement the budgetary control in the public finances system is proposed. Problems of budget control are identified. Types of budget control are outlined, which, once applied, will enable to improve its practice.